PKM Peran Strategis BUMDes dalam Mengatasi Kendala Produksi dan Pemasaran UMKM Emping Melinjo: Pengalaman Emping Melinjo Bu Hj Eha, Kecamatan Taktakan - Hamidah Hamidah; Jaka Wijaya Kusuma; Yudi Nur Supriadi; Guntur Syahputra Saragih; Siti Fatonah; Nugrahini Kusumawati; Dini Martinda Lestari (Yayasan Education and Social Center, 2026)
This community service project aims to analyze the strategic role of Village-Owned Enterprises (BUMDes) in addressing production and marketing challenges faced by micro, small, and medium enterprises (MSMEs) producing melinjo crackers, using a case study of Bu Hj Eha’s Melinjo Cracker Business in Taktakan Subdistrict. MSMEs producing melinjo crackers in this region face various challenges, including fluctuations in the supply and quality of raw materials, limited access to efficient production technology, suboptimal hygiene standards, as well as challenges related to market reach, branding, packaging, and the utilization of digital marketing. This community service project employed a qualitative approach using a case study design, involving in-depth interviews with MSME owners, BUMDes administrators, and workers, as well as field observations. The findings indicate that BUMDes has significant potential to play a role in facilitating collective raw material procurement, supporting the provision and management of shared production equipment, organizing training, and assisting in the development of collective village branding and packaging. Furthermore, BUMDes can serve as key facilitators in the adoption of digital marketing technologies and the opening of new market access. However, the role of BUMDes is currently still in the early stages of development, requiring capacity building for management, more structured programs, and more synergistic collaboration. Key recommendations include strengthening BUMDes capacity, developing well-planned support programs for MSMEs, establishing a collective village brand, and utilizing digital platforms. This community service project concludes that BUMDes is a crucial strategic instrument in empowering melinjo emping MSMEs and strengthening the village economic ecosystem in Taktakan Subdistrict